Current insights into the diagnosis and management of melanocytic choroidal tumors: a short review - Zwolińska, Emilia; Konstantinidis, Lazaros; Rospond-Kubiak, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
We aimed to review methods that facilitate early identification of malignant potential of choroidal melanocytic lesions. Shields’ mnemotechnic “To Find Small Ocular Melanoma” (TFSOM) evolved through “To Find Small Ocular Melanoma Using Helpful Hints Daily” (TFSOM-UHHD) to “To Find Small Ocular Melanoma Doing Imaging” (TFSOM-DiM), using multimodal imaging data to evaluate the character of the melanocytic lesion. Damato’s MOLES scoring also uses multimodal imaging data but, in contrast to the former, does not require ultrasound examination for the evaluation. It thus offers a simple diagnostic tool for optometrists and ophthalmologists, reducing unnecessary referrals to tertiary care centers. Surgical diagnosis via choroidal biopsy is reserved for equivocal cases of the tumors. Fine needle aspiration (FNAB) or vitreous cutter biopsy aids in prognosis and personalized treatment. While choroidal melanoma (CM) diagnosis and risk assessment tools have improved, early detection remains pivotal for enhancing patient survival. Therefore, knowledge of recent assessment methods is of inestimable importance for every clinician.